Diving in the code of Joomla : release 2.5 - Δρούγκας, Κωνσταντίνος (Science, 2013)
Diving in the code of Joomla examines in a deep and detailed manner the internal code of Joomla and its expansion abilities. It also provides the reader with detailed examples in order to create his/her own Joomla add-ons (components, modules and plug-ins). Finally, it analyzes the whole procedure for the setting of a debugging environment. This book describes step by step the execution of a Joomla session, from its first to the last command. Joomla has seven phases which are analytically presented in it. For the first time in a book can the reader receive such a detailed presentation of the code execution. Every stage of the execution is explained in a clear and thorough way producing a real case study for one of the largest software packages (Content Management System, Joomla). The most important parts of the code and the key commands of every phase are decoded in front of the reader. Dive in the code of Joomla, acquire a comprehensive view about its internal code and make your own extensions!